Mitomycin C as an adjunct in the treatment of localised ocular surface squamous neoplasia. Issue 1 (23rd December 2003) - Chen, C; Louis, D; Dodd, T; Muecke, J
Abstract : Aim: To report the outcome of topical mitomycin C (MMC) used as adjunctive treatment following primary excision of ocular surface squamous neoplasia (OSSN). Method: Prospective, non-comparative interventional case series of 27 primary OSSN lesions from 26 patients treated in a single ocular oncology centre over a 4 year period. Result: 27 cases of OSSN received a treatment regimen of surgical excision, followed by topical MMC. Mean follow up of 27 (SD 12) months (range 12–50, median 25 months) revealed zero recurrences. Conclusion: MMC treatment following surgical excision decreases the recurrence rate of primary ocular surface neoplasia and should be considered as adjunctive therapy in primary treatment.